False data filtering algorithm without relying on MAC authentication for wireless sensor networks - YI Ye-qing1; LIN Ya-ping1; PENG Ge1; ZHOU Si-wang2; YANG Si-qing1 (Tongxin xuebao)
A multiple semi-fragile watermarks algorithms was proposed,considering the characteristics of clustering col-laboration aggregation in WSN.The generation of watermarks,embeding and extraction were completed by not a single node,but a fixed number of witnesses nodes which selected within the same clusters.This algorithm could against leak-age of keys when a single node was captured,and it could save energy costs also.On this basis,a false data filtering al-gorithm was proposed based on multiple semi-fragile watermarks,this algorithm could authenticate the accuracy,com-pleteness and fresh using watermarks embedded in data,without relying on MAC authentication.It provided a compari-son between the scheme and previously proposed schemes.The analysis and simulation results indicate significant im-provement in probability of filtering false data,energy saving and having robust,yet fragile characteristics,which support lossy in-network data processing and resist of the noise in certain.